ISOLATION AND IDENTIFICATION OF FUNGAL SPECIES FROM SPOILED FRUITS IN UTAKO MARKET, ABUJA, NIGERIA - Mairami, Fatima; Abdullahi, Samira Abdulmudallib (FUDMA JOURNAL OF SCIENCES, 2026)
Fruits inherently harbor a diverse range of microorganisms, including various pathogens like fungi. Food spoilage is a complex process, and excessive amounts of food are lost due to microbial spoilage, even with modern-day preservation techniques. This research investigated the different types of fungal species associated with fruit spoilage at the Utako market in Abuja, Nigeria.  A total of one hundred fruits—seventy spoiled and thirty healthy—were collected from the market and brought to the lab. A sterile blade was used to cut thin slices of the rotting fruits, which were then inoculated onto PDA media and incubated for five days at 27 oC. Aspergillus niger, A. flavus, A. fumigatus, Aspergillus spp., Rhizopus spp., Mucor spp., and Alternaria spp. were the seven distinct fungal species found in the results. Alternaria is the least common species, whereas Aspergillus niger is the most common species.  However, Alternaria has the lowest pathogenicity, whereas Rhizopus spp. have the highest. Some of these fungal species have strains that are known to produce toxins and have the potential to cause serious food poisoning.
Keywords: Abuja; Isolates; Fungi; Utako